Green composites from castor oil and renewable reinforcing materials: maleated castor oil-polystyrene matrix reinforced with greige fibre - Ferreira, Lizé-Mari (Department of Mechanical Engineering, 2020)
The need to find biodegradable alternatives for common polymer materials has risen due to the increase in pollution (soil and water) and the effects that it has on the ocean and wildlife. Alternatives can be found by turning to plant-based oils, for example castor oil, to be used in the synthesis of a variety of monomers. Castor oil is suitable as it is non-edible; thus its use does not deplete food sources and it has high chemical reactivity. In this study, medical grade castor oil was maleated by the addition of maleic anhydride to form maleated castor oil (MACO). This reaction was performed at 98 ˚C for five hours. The completion of the reaction was monitored using acid value. The maleated castor oil was reacted with styrene monomer (at 60 ˚C) and thermally cured to form a tough but flexible polymer (MACOPS). Curing took place for two hours at 90 ˚C, two hours at 120 ˚C and 1 hour at 160 ˚C. Additionally, the synthesized polymer matrix was reinforced with alkalized greige fibres (consisting of a hemp and cotton mix) using a hand lay-up process. Mechanical tests - tensile, flexural and impact strength - were performed on the neat and reinforced polymer. Comparison tests (to determine mechanical properties) were also conducted on commercial general purpose polystyrene (GPPS) and high impact polystyrene (HIPS). Scanning electron microscopy (SEM) was performed on the tensile fracture surfaces of the reinforced matrix. The crosslink density, contact angles and density of the synthesized polymer were determined. Differential scanning calorimetry (DSC) was used to determine the glass transition temperature(s) of the synthesized and commercial polymers. Thermogravimetry was performed on the synthesized matrix as well as the commercial polymers to determine operating temperatures. Raman spectroscopy was used to obtain structural information on the synthesized polymer as well as confirm the successful completion of the maleation reaction. To test for the compostability of the maleated castor oil-polystyrene polymer matrix, biodegradability tests were conducted for a period of ten weeks. The degraded samples underwent tensile testing and the contact angles were determined. Transmission electron microscopy (TEM) was used to see the distribution of polystyrene throughout HIPS and the MACOPS matrix. The acid value at the start of the reaction was 80.1/100 mgNaOH and at the end of the reaction the acid value decreased to 74.7/100 mgNaOH. A decrease in acid value indicated that the maleic anhydride stopped reacting at the end of the reaction. An increase in viscosity of the mixture served as an indication that the maleation reaction did take place. ASTM D6110 was used for the Charpy impact test. HIPS performed as expected with the highest impact strength of 58.4 kJ/m2 . The addition of MACO to styrene monomer led to an increase in the toughness of the end product. An increase was observed for both the MACOPS and reinforced MACOPS compared to GPPS. MACOPS and reinforced MACOPS had impact strengths of 41.5 kJ/m2 and 45.0 kJ/m2 respectively. The addition of the reinforcing greige fibres did not significantly improve the impact strength. GPPS had the lowest impact strength of 33.9 kJ/m2 . Tensile tests were conducted according to ASTM D638. For MACOPS an ultimate tensile strength (UTS) of 23.0 MPa and a Young's modulus of 983 MPa were found. GPPS on the other hand had a much higher UTS and Young's modulus of 44.8 MPa and 3.3 GPa respectively. Once again the MACOPS had tensile properties closer to those of HIPS. The UTS and Young's modulus of HIPS was 13.5 MPa and 1.5 GPa respectively. The reinforced MACOPS did not perform very well under tension with a UTS of 13.1 MPa and a Young's modulus of only 283 MPa. The theoretical modulus of the composite was calculated using the Rule of Mixtures and the Halpin-Tsai model to determine the efficiency of the greige fibres as reinforcement. The efficiency was determined to be less than 30%. Flexural tests were conducted according to ASTM D7264. A significant difference in the flexibility of the synthesized polymer was found when compared to GPPS. MACOPS had a maximum flexural strength of 22.1 MPa whereas GPPS had a flexural strength of 74.4 MPa. The MACOPS had flexural properties closer to that of HIPS which had a flexural strength of 27.2 MPa. The reinforced MACOPS had a flexural strength of 12.2 MPa. This was ascribed to the presence of significant delamination. GPPS and HIPS have no crosslinks between the polymer chains. A crosslink density of 2.1 x 10-3 mol/cm3 was determined for the MACOPS matrix. This could point to co-polymer formation between MACO and polystyrene. Raman spectroscopy was used to determine if the maleation of castor oil took place successfully. Maleic anhydride has signature absorption bands at 1850 cm-1 and 1790 cm-1 . These peaks were absent in the MACO spectrum, which suggests complete reaction. Signature peaks of both the MACO and GPPS were present in the spectrum of MACOPS. This also may point to co-polymer formation. A Raman map of MACOPS showed uniform distribution of polystyrene throughout the sample whereas HIPS had numerous gaps where polystyrene was of low intensity. This points to the presence of sections containing polybutadiene. Therefore MACOPS can be characterized as either a co-polymer or an interpenetrating polymer network. MACOPS displayed two glass transition temperatures (Tg) when analyzed with DSC. A small (low intensity) glass transition temperature peak was observed at 93.2 °C and a second of higher intensity at 54.9 ˚C. Two glass transition temperature can point to an interpenetrating polymer network. The Tg of 54.9 ˚C was assigned to a co-polymer. The Tg of 93.2 ˚C is possibly due to a small amount of homo-polymerized polystyrene. Due to the fact that the glass transition temperature is relatively close to ambient temperature, the matrix is relatively flexible but not elastomeric; hard and tough but not very brittle. Thermogravimetry indicated a thermal degradation onset temperature of 336 °C for the MACOPS matrix. The onset temperature for thermal degradation of MACOPS is lower than those of HIPS and GPPS. After biodegradability testing, no significant loss in mechanical properties was observed for the MACOPS matrix and reinforced composite. MACOPS showed the most mass loss (10.4%) in comparison with the other materials. A significant decrease was seen in the contact angle measurements of the degraded reinforced MACOPS. The contact angle decreased from 88˚ (original) to 54.2˚ (degraded). This points to surface changes as a result of degradation that decreases the hydrophobicity of the material. It can be seen that the addition of MACO to styrene monomer most likely results in an IPN with a degree of crosslinking. The properties of this matrix is closer to those of HIPS than GPPS. The matrix is hard, tough and more flexible than GPPS. At room temperature the MACOPS matrix is used just above its glass transition temperature. Reinforcing the matrix with greige fibres led to a decrease in mechanical properties. Thus the fibres acted only as a filler. The synthesized MACOPS matrix is hydrophilic and shows no significant degradation when placed in compost after a period of 10 weeks.